Kajiansudut inklinasi gigi molar ketiga rahangbawahpre-erupsi pada kelompok umur14 -17 tahun(The pre-eruptedstudyof mandibular thirdmolar inclinationamong 14 to 17 year old) - Nurlailia DS; Mei Syafriadi (DiscoverSys Inc., 2014)
At the beginning of the growth, tooth inclination is mesioangular, then move gradually to come into contact with thedistal surface of the second molar and further commit to sliding movement parallel to second molar axis. This positionwill be retained to achieve the eruption way to oral cavity. However, the last decade reported incidence increasedimpaction of the third molar teeth in the lower jaw. This study was aimed to study the level of pre-eruption of mandibularthird molar in the population group aged 14-17 years to predict the risk of tooth impaction or not. Differentiatedpopulations on cluster I, age 14-15 years old; group II, 15.1-16 years old; and group III 16.1-17 years old. Researchcarried out by clinical observation and measurement of at Department of Radiology in Jember University with 48people selected based on predetermined criteria. X-ray projection was exposed by paralleling technique on the lowerthird molar teeth, left and right. The results showed 43.75% of 14-15 year old group had the third molar angle interval50-56°; 15.1-16 year age group, 80% have 57-70° angle interval, and 16.1-17 years age group, 46.67% has angularinterval 64-70°. It was concluded that a large interval of the third molar angle increase due to the increased of age,and the angle is different between groups based on gender.